Evidence of new particle formation during post monsoon season over a high-altitude site of the Western Ghats, India. Issue 4 (21st April 2017) - Leena, Parakkatt Parambil; Anil Kumar, Vasudevan; Dani, Kundan. K.; Sombawne, Sunil. M.; Murugavel, Palani; Pandithurai, Govindan
ABSTRACT: The formation of ultrafine particles, their growth, and associated characteristic features has been studied during new particle formation events over a high-altitude station of the Western Ghats during the 2014 post-monsoon season. Most of the events were observed during noon time where particle bursts in the nucleation-mode size range from 5 to 25 nm followed by sustained growth in size. This phenomenon persists for ∼4–8 h with a growth rate of 1–2 nm h – 1 . Peak concentrations of nucleation-mode particles during the event generally vary from 2300 to 5000 cm – 3 . The mean growth rate is 1.4 ± 0.42 nm h – 1, particle formation rate is 1.14 ± 0.22 cm – 3 s – 1, coagulation sink is 0.35 ± 0.22 cm – 3 s – 1, and condensational sink is 15.4 ± 2.6 × 10 – 3 s – 1 . All these values are comparable with earlier results from Indian region. Comparison of size-segregated particle number concentration during days of new particle formation events and those without new particle formation were carried out showing a distinct variation in nucleation and Aitken mode with least variability associated with the accumulation mode.